2005
DOI: 10.1007/s10573-005-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Inerting of Methane-Air Mixtures by Compositions Based on Carbon Dioxide and Nitrogen with Addition of Halocarbons

Abstract: Conditions of inerting of methane-air mixtures by carbon dioxide and nitrogen with addition of CF 3 Br, C 2 F 4 Br 2 , and CF 3 I are examined. The value of the minimum inerting concentration of the inerting substance is significantly reduced by introduction of these substances [up to 15%(vol.)] to N 2 and CO 2 . A further increase in CF 3 Br and C 2 F 4 Br 2 concentrations does not reduce the minimum inerting concentration, and an increase in the concentration of CF 3 I above 15%(vol.) drastically increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The investigation on the effect of concentration of methane in biogas when it is used as a fuel for a spark ignition engine was reported by Porpatham et al [34]. Other studies revealed the effect of additives (N 2 , Ar, H 2 O or CO 2 ) on CH 4 /air, CH 4 /CO 2 /air and CH 4 /O 2 /H 2 /inert flames [35][36][37][38][39][40][41]. The attention of other researchers has been directed towards the combustion characteristics of biogas under hydrogen-enriched conditions [24,[42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 96%
“…The investigation on the effect of concentration of methane in biogas when it is used as a fuel for a spark ignition engine was reported by Porpatham et al [34]. Other studies revealed the effect of additives (N 2 , Ar, H 2 O or CO 2 ) on CH 4 /air, CH 4 /CO 2 /air and CH 4 /O 2 /H 2 /inert flames [35][36][37][38][39][40][41]. The attention of other researchers has been directed towards the combustion characteristics of biogas under hydrogen-enriched conditions [24,[42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 96%
“…This question was studied in more detail by Takahashi, Urano, Tokuhashi, and Kondo (2003). It was found (Coward & Jones, 1952;Zabetakis, 1965) that an ignition source in the form of an electrical spark of the energy not less than 1 J is sufficient for the reliable determination of the flammability limits at atmospheric pressure, and only for very low pressures (less than 10 kPa) and in some special cases (combustion of halogenated agents in air) more powerful ignition sources are required (Lisochkin & Poznyak, 2001b;Lisochkin, Poznyak, & Belevteev, 1999;Lisochkin, Poznyak, Belevteev, & Kunina, 2003). The pressure criterion for ignition used in this study was verified earlier (see, for example, and works cited there).…”
Section: Methodsmentioning
confidence: 99%
“…In their research of gas explosion suppression technology, Li et al [8][9][10] investigated inert gas suppression approaches to restrain the continuous spread of explosive gas, such as the use of nitrogen, among other suppressants, as an inhibitor to prevent the flame from spreading, finding that the suppression is a result of inertia isolation rather than inert gas dilution. Ya Lisochkin et al [11] studied the inertness of a methane-air mixture based on the composition of carbon dioxide and nitrogen, combined with halogenated carbon (CF3Br, C2F4Br2, and CF3). When the concentration of CF3I increased to more than 15% in volume, it would increase sharply to higher than the minimum inert concentration of pure nitrogen.…”
Section: Introductionmentioning
confidence: 99%